ANALISIS RASIO KEUANGAN UNTUK MENGUKUR PREDIKSI FINANCIAL DISTRESS (Studi Kasus pada Salah Satu BUMD di Provinsi Banten) - Budi Mulyati; Toni Anwar Mahmud (Universitas Pamulang, 2020)
The portion of state expenditure for regional government tends to decrease, so the government hopes that regional governments could optimize the potential of their regions to increase their income by obtaining other revenues from BUMD. This study aims to determine the prediction of financial distressing in one of the regional companies in Banten province. This research used quantitative descriptive method. Data were collected from financial statements from 2015 to 2019. Data were analyzed by quantitative techniques using the Altman Z Score. Based on the results, it were found that the score of the Z Score has a positive trend score. The Z score obtained in 2015 was 1.50; in 2016 it was 1.65; in 2017 3.08; in 2018 it is 3.38 and in 2019 it is 3.11.